2021
DOI: 10.3390/ma14206208
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Acid Resistance of Ceramic-Based Self-Compacting Alkali-Activated Concrete: Optimizing and Predicting Assessment

Abstract: The development of self-compacting alkali-activated concrete (SCAAC) has become a hot topic in the scientific community; however, most of the existing literature focuses on the utilization of fly ash (FA), ground blast furnace slag (GBFS), silica fume (SF), and rice husk ash (RHA) as the binder. In this study, both the experimental and theoretical assessments using response surface methodology (RSM) were taken into account to optimize and predict the optimal content of ceramic waste powder (CWP) in GBFS-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Algaifi et al used the response surface methodology to optimize and predict the optimal content of CWP in BFSbased self-consolidating alkali-activated concrete. The authors found that the optimum content of 31% CWP satisfied the desired mechanical and durability performance, particularly when specimens were exposed to acid attack [18]. Teimortashlu et al employed the Taguchi method to optimize the compressive strength of tertiary blended selfcompacting concrete, in which three factors at four different levels were considered [19].…”
Section: -2mentioning
confidence: 99%
“…Algaifi et al used the response surface methodology to optimize and predict the optimal content of CWP in BFSbased self-consolidating alkali-activated concrete. The authors found that the optimum content of 31% CWP satisfied the desired mechanical and durability performance, particularly when specimens were exposed to acid attack [18]. Teimortashlu et al employed the Taguchi method to optimize the compressive strength of tertiary blended selfcompacting concrete, in which three factors at four different levels were considered [19].…”
Section: -2mentioning
confidence: 99%
“…Recently, researchers proposed and developed a technique for global optimization by combining experimental design with machine learning (ML) [12]. The ML approach uses various dependent and independent variables gathered from experimental design [13]. Lately, the deployment of ML and AI approaches has been reported in various chemical processes, such as separation [14], transesterification reactions [15,16], bioethanol production processes [17], electrospinning processes [18], polymerization processes [19], esterification reactions [20], and other chemical processes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, concrete is the most consumed human-made material, with global consumption of up to 15 billion tons of natural aggregates every year [5,6]. The utilization of waste materials can help our environment by reducing the consumption of non-renewable natural resources, lessening the problems of landfills [7,8]. Conservative usage of natural resources and reducing the waste generated by the industry are among the main strategies to attain cleaner and more sustainable productions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%